The Business Model Navigator - Gassmann, Oliver (Pearson Education, Limited, 2020)
A strong business model is the bedrock to business success. But all too often we fail to adapt, clinging to outdated business models that are no longerpromisingthe results we need. This new edition builds on the well-known methodology of the first edition to allow you to innovate,